Given
![y=f(x)=2x^3+8x^2-2x-8](https://img.qammunity.org/2023/formulas/mathematics/college/6g73i1lgwtywolqvcs1r3hu1885xt0rnrv.png)
Find
x-intercept and y-intercept
Step-by-step explanation
To find the y intercept, put x=0 in the above equation
![\begin{gathered} y=f(x)=2(0)^3+8(0)^2-2(0)-8 \\ y=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k43i05aiu9tix880sv8ziv4m6xb1j7a9c8.png)
Now Finding x intercept
![\begin{gathered} f(x)=2x^3+8x^2-2x-8 \\ f(1)=2(1)^3+8(1)^2-2(1)-8 \\ f(1)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vq0eqvhfpnyv3b1l25g64l2en1x7mrtnsb.png)
Therefore x-1 is a factor of the above equation
Divide f(x) with x-1, we get
![\begin{gathered} (2x^3+8x^2-2x-8)/(x-1) \\ =2x^2+10x+8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/djhfpqurpnzr893t15hwjip699k7bcfx3c.png)
Now finding the factors of this quadratic equation
![\begin{gathered} 2x^2+10x+8=0 \\ 2x^2+8x+2x+8=0 \\ 2x(x+4)+2(x+4)=0 \\ (x+4)(2x+2)=0 \\ (x+4)(x+1)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dpqs3cbe4pzxm40l59xqryuy4j51cfi5s1.png)
Therefore,
x=-4,-1
Final Answer
x-intercepts = 1,-1,-4
y-intercepts= -8